Global burden of colorectal cancer from 1990 to 2021: a systematic analysis from the Global Burden of Disease Study 2021 - Chen, Xue; Tian, Rui; Chen, Ze; Quan, Longfang; Bei, Shaosheng (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC), currently the second leading cause of cancer-related mortality worldwide, poses a significant burden on public health. This study systematically analyzes the temporal trends in CRC disease burden based on Global Burden of Disease (GBD) data from 1990 to 2021, aiming to provide robust evidence for epidemiological research, disease prevention, and the formulation of public health policies.MethodsThis study analyzed CRC incidence, mortality, and disability-adjusted life years (DALYs) using GBD1990–2021 data. Temporal trends were evaluated via estimated annual percentage changes (EAPC), with Pearson correlation assessing Socio-demographic Index (SDI) associations. Projections of global CRC epidemiology through 2035 were developed to inform public health strategies.ResultsIn 2021, global CRC accounted for 2,194,143 incident cases, 1,044,072 deaths, and 24,401,100 DALYs. CRC remains a major public health challenge worldwide. From 1990 to 2021, age-standardized incidence rates (ASIR) increased (EAPC = 0.15, 95% CI: 0.12–0.19), while mortality (EAPC=−0.81, −0.84 to −0.77) and DALY rates (EAPC=−0.83, −0.87 to −0.80) declined significantly. Notable socioeconomic gradients were observed across the spectrum of regions. Geographic disparities were prominent: high-SDI regions had the highest ASIR (40.525, 37.445–42.447 per 100,000), whereas high-middle-SDI regions showed peak mortality (15.709, 14.144–17.25) and DALY rates (338.225, 316.751–354.913). Males and individuals aged >85 years experienced disproportionate burden increases. By 2035, the global burden of CRC is projected to maintain its current upward trajectory.ConclusionsGlobally, CRC’s ASIR has gradually increased, while age-standardized death rate (ASDR) and DALY rates have declined significantly, reflecting an overall reduction in disease burden. Regions with higher SDI, male predominance, and aging populations contribute most to rising CRC cases. Despite progress in mortality reduction, CRC prevention and control will continue to pose significant public health challenges in the coming years.